Tokopedia's Legal Responsibility to Consumers for Non-Compliance of Electronic Goods in the Online Trading System - Ginting, Meilani Amanda; Sidauruk, Jinner; Gultom, Meli Hertati (Journal of Legal and Cultural Analytics, 2025)
This study discusses Tokopedia's legal responsibility to consumers for the non-conformity of electronic goods in the online trading system. Although regulations regarding consumer protection have been established, there are still losses incurred from e-commerce platforms that do not provide legal accountability in accordance with the laws and regulations. Consumers often experience losses due to products received that do not match the product descriptions made by businesses on Tokopedia. Although there are regulations governing consumer protection, such as Law No. 8 of 1999 on Consumer Protection and Law No. 11 of 2008 on Information and Electronic Transactions (ITE Law), many consumers still suffer losses due to the inadequate supervision and dispute resolution systems provided by the platform. This study employs a normative legal method with a regulatory approach and a conceptual approach. The findings indicate that Tokopedia bears civil, administrative, and in certain circumstances criminal legal liability, and that consumers have the right to pursue legal action both through litigation and non-litigation means. An evaluation and reformulation of the system are needed to strengthen consumers' position within the e-commerce ecosystem.